Analisis Bahaya Gempa Bumi Menggunakan Metode Probabilistic Seismic Hazard Analysis Di Wilayah Likupang, Minahasa Utara - Rini Indri; Heindrich Taunaumang; Farly Reynol Tumimomor (Jurnal FisTa : Fisika dan Terapannya, 2022)
The Probabilistic Seismic Hazard Analysis (PSHA) method is a method used in seismic hazard analysis based on the definition of a probability distribution function that takes into account and combines the uncertainties of the earthquake event scale, location, and frequency of occurrence, to obtain a comprehensive picture of the hazard level or a location that reviewed. The Likupang area, North Minahasa is a location that is prone to earthquake disasters, for this reason, early mitigation is needed, one of which is mapping the potential for disaster hazards. Maximum ground vibration acceleration (PGA) is the greatest value of ground acceleration at a place caused by earthquake vibrations in a certain period of time. In this study, the results of the PSHA calculation in the North Minahasa Likupang area were obtained, the largest PGA value was 1.4g–1.8g, tilapia SA T= 0.2 seconds was 1.7g-2.1 and SA T=1 value, 0 seconds is 0.5g – 0.6g. Based on these results, the danger of light to severe damage can be caused.